2015
DOI: 10.1097/mat.0000000000000282
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Life Support for Refractory Cardiac Arrest or Shock

Abstract: We aimed to identify factors associated with hospital mortality among patients receiving extracorporeal life support (ECLS). All consecutive patients treated with ECLS for refractory cardiac arrest or shock in the Caen University Hospital in northwestern France during the last decade were included in a retrospective cohort study. Sixty-four patients were included: 29 with refractory cardiac arrest and 35 with refractory shock. The main reasons for ECLS were acute coronary syndrome (n = 23) and severe poisoning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…It showed better survival in the group treated by VA-ECMO and multivariate analyses identified VA-ECMO as one of the independent factors of survival [24]. Other non-controlled retrospective studies have reported a survival of between 25 and 75% in patients with cardiotoxicant poisonings treated by VA-ECMO [240][241][242][243][244][245]. A registry study showed improvement of haemodynamic and metabolic parameters of cardiotoxicant-poisoned patients treated by VA-ECMO [246].…”
Section: Question 83: Should Extracorporeal Life Support Be Used In mentioning
confidence: 93%
“…It showed better survival in the group treated by VA-ECMO and multivariate analyses identified VA-ECMO as one of the independent factors of survival [24]. Other non-controlled retrospective studies have reported a survival of between 25 and 75% in patients with cardiotoxicant poisonings treated by VA-ECMO [240][241][242][243][244][245]. A registry study showed improvement of haemodynamic and metabolic parameters of cardiotoxicant-poisoned patients treated by VA-ECMO [246].…”
Section: Question 83: Should Extracorporeal Life Support Be Used In mentioning
confidence: 93%
“…ECMO was performed only after admission into the Caen University Hospital, where medical teams and nurses have extensive experience with emergency extracorporeal life support. [15][16][17] The hardware consisted of a Biomedicus (Medtronic, Minneapolis, Minnesota) or Maquet (Rotaflow, Jostra-Maquet, France) portable system incorporat-ing a centrifugal pump console. The closed ECMO circuit consisted of preconnected polyvinyl chloride tubing (Medtronic or PLS 20-50 [Maquet]) having a hollow-fiber membrane oxygenator with an integrated heat exchanger.…”
Section: Cannulation Technique and Management During Ecmomentioning
confidence: 99%
“…These two patients presented with local bleeding complications. The time between ingestion was 4 [2][3][4][5][6][7] h and the duration of ECMO was 4 [2-5] d. ECMO was started 3 [(-1)-5] h after the theoretical peak plasma level. The mean of the SAVE-score was -6, the mean survival predicted by the SAVE-score was 30%, but the observed survival was 70%.…”
Section: Resultsmentioning
confidence: 99%
“…Sometimes intoxication requires more aggressive treatment, such as venous-arterial extracorporeal membrane oxygenation (VA-ECMO). [3,4] For refractory cardiac arrest or shock, drug intoxication is independently associated with survival, [5] and treatment with VA-ECMO could improve survival. [6] Prompt implementations of ECMO could improve the prognosis.…”
Section: Introductionmentioning
confidence: 99%